PENERAPAN ARSITEKTUR MODEREN RUSTIC PADA PERANCANGAN RESTORAN DAN BUTIK DI SAMARINDA - Thamrin, Nur Husniah; HS, Cisyulia Octavia; Rulia, Anna; Kurniawati, Dahniar (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
The development of the Nusantara Capital City (IKN) in East Kalimantan has been a significant catalyst for economic growth and lifestyle changes in surrounding areas, including the city of Samarinda. The increasing awareness of modern lifestyles and the desire for new experiences has led Samarinda's consumers to seek out places that not only provide products or food but also offer a comfortable atmosphere and visually appealing aesthetics. The objective of this research is to develop a design concept for a commercial building that combines two functions: a restaurant and a boutique, using a modern rustic style as a response to this trend. This study employs a qualitative analysis method, combining the results of literature reviews, field surveys, internet studies, and comparative studies of similar buildings, aiming to identify the unique characteristics of modern rustic architecture that suit the needs of building users, functionality, and site conditions. The site is determined through an analysis of several alternative sites. The results of this analysis are a design concept for a restaurant and boutique building with a modern rustic architectural style, evident in both the building's facade and interior. The design concept produced in this research is a unique blend of modern, clean lines and the warmth of rustic materials, resulting in a visually and functionally aesthetic space.